Analysis of Raw Material Potential Based on Leading Commodities for Sustainable Industrial Development in East Java - Kartika Simah Bengi; Ahyahudin Sodri; Dwi Nomo Martono (Jurnal Penelitian Pendidikan IPA, 2025)
This study evaluates the potential of molasses (sugarcane molasses) as the main feedstock for bioethanol production with a capacity of 100 kiloliters per day at PT Enaro Mojokerto. Assuming a fermentation efficiency of 90% and a theoretical sugar-to-ethanol conversion ratio of 0.511 kg ethanol per kg sugar, the required sugar is approximately 171.559 kg/day, corresponding to 343 tons of molasses (with 50% sugar content) to produce 100 KL of ethanol per day. Literature review and secondary data collection were conducted to evaluate three main criteria: feedstock availability, supply continuity, and fermentable sugar content. The analysis results indicate that East Java has a molasses production potential of 660,000 tons/year from 15 active sugar mills, with the highest concentration in Malang, Kediri, and Mojokerto regencies. This study concludes that the development of the molasses-based bioethanol industry in Mojokerto is technically and economically feasible with integrated supply chain management support.